Morphological evaluation and comparative study of pollen viability of different promising genotypes of sesame (Sesamum indicum L.): Morphological evaluation and comparative study of pollen viability of different promising genotypes of sesame (Sesamum indicum L.) - ADIL IQBAL,; JHILIK CHOWDHURY,; TAMINA BEGUM,; TAPASH DASGUPTA, (Journal of Oilseeds Research, 2020)
The present investigation was carried out to evaluate 21 genotypes of sesame on the basis of 8 morphological characters to assess the pollen viability of the selected promising genotypes as well the ideal time for maximum pollen viability. Pollen viability was assessed at three different times, viz., 7.45 a.m., 11.00 a.m. and 12.45 p.m. Based on morphological characters all the genotypes were grouped into 3 major clusters. Depending upon genetic distance seven promising genotypes were selected from different clusters for future crossing program. The average pollen viability of these seven promising parents was 85.57% at 7.45 a.m. followed by 72.55% at 11.00 a.m. and 63.84% at 12.45 p.m. Maximum pollen viability was observed in the morning hours i.e. at 7.45 a.m. Interestingly, out of the selected genotypes, the wild species, Sesamum mulayanam showed significantly more pollen viability percentage (96.61%) at 7.45 a.m. as compared to the genotypes belonging to the cultivated species, indicating its potential as a good pollinator.